2016
DOI: 10.1111/pbr.12383
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Lr56 translocation recombinants in wheat

Abstract: In an attempt to transfer the Lr56/Yr38 resistance loci from Aegilops sharonensis to wheat, a 6A‐6Ssh chromosome translocation was produced. It involves essentially the entire chromosome 6Ssh with a small terminal segment of 6AL. Induced homoeologous recombination of the translocated chromosome with 6A produced numerous recombinants including three recombined chromosomes carrying Lr56 that could not be precisely mapped for lack of suitable markers. This study aimed to determine the chromosomal locations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Substantially shortened versions of the Lr59 (Pirseyedi et al, 2015), Lr56 (Somo et al, 2016), and Lr62 (current study) translocations have been identified. Another 6BS translocation ( Lr53 from Triticum dicoccoides ) has been described by Marais et al (2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantially shortened versions of the Lr59 (Pirseyedi et al, 2015), Lr56 (Somo et al, 2016), and Lr62 (current study) translocations have been identified. Another 6BS translocation ( Lr53 from Triticum dicoccoides ) has been described by Marais et al (2005).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the introgressed regions always included an alien homoeo‐locus of the Xdupw217 marker locus (Table 2), and, in the case of translocations involving the 6BS chromosome arm, it had replaced the corresponding wheat locus. Marker information pertaining to the Lr56 ‐157 (Somo et al, 2016) and Lr62 ‐135 translocations on 6AS are compared in Table 3, which shows their similar locations. These findings suggest that Lr62 ‐135 is a comparatively large translocation.…”
Section: Resultsmentioning
confidence: 99%
“…Three catalogued Lr genes, Lr56, Lr62 (Marais et al 2008), and Lr64 (Kolmer et al 2010), and two QTLs, IWA680_6AS and 6A_t1 (Gao et al 2016; Turner et al, 2016) have already been detected on chromosome 6A for leaf rust resistance. Lr56, Lr62 , and Lr64 are seedling resistance genes originated from Aegilops sharonensis, Aegilops neglecta and, Triticum dicoccoides , respectively (Somo et al 2016; Kolmer et al 2010). Due to the lack of genetic materials that carries these genes in our GWAS panel, it is unlikely that this locus represents Lr56, Lr62 , and Lr64.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of recombinant Lr62 ‐129, Xdupw217 negl (251 bp) had replaced the common wheat Xdupw217 aest locus on 6BS and thus can also be used as a codominant marker. In 15 wheat genotypes that have been studied so far (Somo et al, 2016), the Xdupw217 aest allele was smaller than in the alien translocations and associated with amplification products of sizes null, 230, 240, and 242 bp; however, this may not be true for all wheat genotypes.…”
Section: Characteristicsmentioning
confidence: 90%
“…sharonensis chromatin (and lacked Yr38 ) were identified. Continued physical and genetic mapping in association with genomic in situ hybridization (GISH) showed that Lr56 ‐157 is the shortest of the three recombined translocations and that it occurs within the 6AS telomeric region (Somo et al, 2016).…”
Section: Characteristicsmentioning
confidence: 99%